The new two-dimensional light scattering method for recognition of pharmaceutical enantiomers - Anton Vladimirovich Syroeshkin, Olga Valerievna Levitskaya, Tatiana Vadimovna Pleteneva, Elena Valerievna Uspenskaya, Maria Antonovna Tribot-Laspiere, Irina Vladimirovna Tarabrina (Journal of Applied Pharmaceutical Science, 2020)
The results of applying the developed mathematical model of the folding of two-dimensional light scattering (2D-LS) patterns into a descriptor to identify the enantiomers of optically active pharmaceutical substances are presented in the article. The following pharmaceutical substances were a subject of this research: L-valine, D-valine, racemic mixture L, D-valine, L-glucose, D-glucose, and L-ascorbic acid. A digital microscope with high spectral density was used to obtain instant 2D-LS patterns. The obtained data were mathematically processed using the original computer program “Vidan”, which uses a mathematical model for the folding of the 2D-LS pattern into descriptors, which are analogs of topological indices in quantitative structure-activity correlations approaches to drug analysis. The 10 descriptors were used as criteria for the difference in the 2D distribution of the scattered light intensity. The use of mono- and multidescriptor analyses allowed us to determine the authenticity of pharmaceutical substances of different classes and their optical isomers. It was found that the dispersion of crystalline substances of optical antipodes up to submicron size led to the leveling of light scattering patterns. The mathematical model was developed and applied for the folding of 2D-LS diagrams into a descriptor. This allowed us to identify the optical antipodes of pharmaceutical substances.
Keywords: Distinction of optical antipodes, two-dimensional light scattering, valine, glucose.